Nxopanxopo wa xitayela xa mutsari eka novhele ya nsuku wa mina na ndzi ta n'wi kuma hi W. R. Chawuke - Mokone, R. L (My University, 2015)
CHAPTER 1: This chapter outlines as follows : The introduction , cause affects, aim of the study, problem statement of the research , value of the research, research method to be used , literature review and definitions of terms. CHAPTER 2: This chapter outlines the detailed biography of the writer W .R. Chauke, summary of literature in the selected books of Nsuku wa mina and Ndzi ta n’wi kuma. CHAPTER 3: In this chapter different types of conflict will be defined and also explain each types. CHAPTER 4: In this chapter we will explain what is characterisation, allegorical figure and caricature. CHAPTER 5: This chapter will focus on the analysing of language and different style of the author in the selected novels. CHAPTER 6: This chapter concludes the research by outlining the findings and giving recommendations.
An analysis of style in W.R. Chawuke's novels nsuku wa mina and ndzi ta n'wi kuma.
Thesis (M.A. (African languages)) -- University of Limpopo, 2015
Keywords: Literature; African languages; Tsonga language -- South Africa -- Limpopo Province